Binding Motifs in the Naked Complexes of Target Amino Acids with an Excerpt of Antitumor Active Biomolecule: An Ion Vibrational Spectroscopy Assay. Issue 7 (23rd December 2020) - Chiavarino, Barbara; Sinha, Rajeev K.; Crestoni, Maria Elisa; Corinti, Davide; Filippi, Antonello; Fraschetti, Caterina; Scuderi, Debora; Maitre, Philippe; Fornarini, Simonetta
Abstract: The structures of proton‐bound complexes of 5, 7‐dimethoxy‐4 H ‐chromen‐4‐one (1 ) and basic amino acids (AAs), namely, histidine (His) and lysine (Lys), have been examined by means of mass spectrometry coupled with IR ion spectroscopy and quantum chemical calculations. This selection of systems is based on the fact that 1 represents a portion of glabrescione B, a natural small molecule of promising antitumor activity, while His and Lys are protein residues lining the cavity of the alleged receptor binding site. These species are thus a model of the bioactive adduct, although clearly the isolated state of the present study bears little resemblance to the complex biological environment. A common feature of [1 +AA+H] + complexes is the presence of a protonated AA bound to neutral 1, in spite of the fact that the gas‐phase basicity of 1 is comparable to those of Lys and His. The carbonyl group of 1 acts as a powerful hydrogen‐bond acceptor. Within [1 +AA+H] + the side‐chain substituents (imidazole group for His and terminal amino group for Lys) present comparable basic properties to those of the α‐amino group, taking part to a cooperative hydrogen‐bond network. Structural assignment, relying on the comparative analysis of the infrared multiple photon dissociation (IRMPD) spectrum and calculated IR spectra for the candidate geometries, derives from an examination over two frequency ranges: 900–1800 and 2900–3700 cm −1 . Information gained from the latter one proved especially valuable, for example, pointing to the contribution of species characterized by an unperturbed carboxylic OH or imidazole NH stretching mode. Abstract : Breaking it down : Neat binding motifs governing the interaction of a bioactive molecule (an excerpt of glabrescione B) with relevant target amino acids (histidine and lysine) are revealed by IR ion spectroscopy at the level of isolated proton‐bound complexes. These noncovalent interactions play a relevant role in directing the preferred protonation site.